2021
DOI: 10.1002/pbc.29265
|View full text |Cite
|
Sign up to set email alerts
|

Association of BRAF V600E mutations with vasoactive intestinal peptide syndrome in MYCN‐amplified neuroblastoma

Abstract: Very rarely, vasoactive intestinal peptide‐related diarrhea (VIP‐D) is observed in patients with high‐risk neuroblastoma (HR‐NB) where the associated fluid and electrolyte abnormalities can pose a major clinical challenge for administering the required aggressive multimodality treatment. Two patients with HR‐NB developed VIP‐D during induction and were found to have a somatic BRAF V600E mutation. Serum VIP levels and diarrhea promptly resolved in both patients after initiating treatment with BRAF and MEK inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Shahid et al identified BRAF V600E mutations in two patients with high-risk neuroblastoma that developed vasoactive intestinal peptide-induced diarrhea (VIP-D) during induction therapy. 10 Notably, the patient in the current report did not experience VIP-D. In another study, investigators found a BRAF V600E mutation to be present in one of 192 neuroblastoma cases, revealing its occurrence in less than 1% of cases.…”
Section: Braf Mutation In Neuroblastoma: a Rare Findingmentioning
confidence: 44%
See 1 more Smart Citation
“…Shahid et al identified BRAF V600E mutations in two patients with high-risk neuroblastoma that developed vasoactive intestinal peptide-induced diarrhea (VIP-D) during induction therapy. 10 Notably, the patient in the current report did not experience VIP-D. In another study, investigators found a BRAF V600E mutation to be present in one of 192 neuroblastoma cases, revealing its occurrence in less than 1% of cases.…”
Section: Braf Mutation In Neuroblastoma: a Rare Findingmentioning
confidence: 44%
“…They concluded that this targeted therapy was compatible with conventional high-risk neuroblastoma therapy and yielded minimal additional toxicities. 10 For the patient in the current report, BRAF inhibition was reserved for the treatment of relapsed disease.…”
Section: Braf Mutation In Neuroblastoma: a Rare Findingmentioning
confidence: 99%
“…In both cases, these therapeutic agents were used in conjunction with conventional high risk therapy. The authors concluded that this targeted therapy was compatible with conventional high risk neuroblastoma therapy and yielded minimal additional toxicities [14]. For the patient in the current report, BRAF inhibition was reserved for the treatment of relapsed disease.…”
Section: Discussionmentioning
confidence: 74%
“…Shahid et al combined dabrafenib with trametinib, a MEK inhibitor, as an adjunct to conventional highrisk therapy to treat VIP-induced diarrhea in two children with BRAF V600E mutations. They concluded that this targeted therapy was compatible with conventional high-risk neuroblastoma therapy and yielded minimal additional toxicities [10]. For the patient in the current report, BRAF inhibition was reserved for the treatment of relapsed disease.…”
mentioning
confidence: 75%
“…Recent studies have identified BRAF mutations in neuroblastoma. Shahid et al identified BRAF V600E mutations in two patients with high-risk neuroblastoma that developed vasoactive intestinal peptide (VIP)-induced diarrhea during induction therapy [10]. In another study, investigators found a BRAF V600E mutation to be present in 1 of 192 neuroblastoma cases, revealing its occurrence in less than 1% of cases [11].…”
mentioning
confidence: 99%